Landwirtschaftliche Betriebssysteme und Kolonisationserfolg in Südbrasilien auf Grund der Forschungen von Leo Waibel - Pfeifer, Gottfried (ERDKUNDE, 1953)
This paper is based on the late Leo Waibel's extensive manuscript which contains the results of his investigations in Southern Brazil. In comparison with other areas of colonisation overseas, the attainments of European colonists in Southern Brazil must largely be considered unsatisfactory or even a failure. Waibel found the key to an understanding of this state of affairs by investigating the agricultural systems employed, which so far have not yet received due attention in literature. By far the greatest proportion of the colonists use the roca-system, an extensive farming system based on clearing forest plots by fire; a system which differs from shifting cultivation proper by the limitation imposed on available land, its size depending on the grant made to a colony. Waibel suggested as a term for this farming system Landwechselwirtschaft (Field change cultivation), and he distinguished primitive and improved versions; the former not involving any application of manure. The latter, which does make use of manuring, can be further divided into two sub-types, one characterised by animal husbandry with improved pastures, the other by a ploughing cultivation. If the colonist succeeds in the changeover to one of the improved systems, his living standard and cultural level improve; but if he remains at the stage of the primitive field change cultivation he becomes impoverished and affected by cultural retrogression; he becomes a caboclo. A genuine success is only achieved if the colonist proceeds to permanent cultivation, which again consists of two sub-types; one with crop rotation without manuring and the other with manuring. Only at the last stage is proper care taken to preserve the inherent fertility of the soil and the cultural level of the colonist readies a satisfactory status. Waibel investigated the particular natural and economic conditions which are responsible for the fact that only 10 per cent, of the colonists have reached this last and optimum stage, whereas 40 per cent, still remain at the stage of the primitive fieldchange cultivation and 50 per cent, at the stage of the improved field-change cultivation. A major reason for the failure of many colonies is found in the problem of the minimale Ackernahrung (minimum size of holding for supporting a family satisfactorily). Assuming that the primitive field-change cultivation is being practised, since for economic reasons the colonists will have to use this farming system in the initial stages, the minimum size of a holding should be about 100 hectares; only then is it possible to use this extensive farming system without exhausting the soil. A review of the development of the land allocations unfortunately reveals that the standard sizes of allocations have declined during the 150 years of the history of colonisation and now stand at 25 hectares. This reduction must be considered a development in the wrong direction. A second important problem, the opening up of the campos of Southern Brazil for agriculture, is also dealt with in Waibel's manuscript. The open grasslands have so far been largely avoided as similarly the prairies in North America were for a long time only reluctantly settled by the European colonists. Basing his conclusions on historical studies and in particular his observations in the colonies Terra Nova and Carambei, Waibel was able to show that it is possible to colonise the campos successfully, necessary conditions being, however, the use of trained farmers and the application of capital. The solution of the problem is therefore to be found in the attraction of colonists of high quality. These now have to be sought also in countries outside Brazil. If Brazil wishes to attract colonists of this calibre, certain conditions must be created, and in the last section of his manuscript Waibel made well thought out, concrete suggestions regarding them. Firstly, contrary to the clauses of the Act of 1938, ethnically uniform colonies should again be permitted; secondly, these colonies should be of settlers of the same religious denomination; and thirdly, the colonies should be provided with the best teachers available.